2015
DOI: 10.1186/s12872-015-0128-8
|View full text |Cite
|
Sign up to set email alerts
|

The rs1803274 polymorphism of the BCHE gene is associated with an increased risk of coronary in-stent restenosis

Abstract: BackgroundWe sought to identify gene polymorphisms that confer susceptibility to in-stent restenosis after coronary artery bare-metal stenting in a Central European population.Methods160 controls without post–percutaneous coronary intervention in-stent restenosis were matched for age, sex, vessel diameter, and diabetes to 160 consecutive cases involving in-stent restenosis of the target lesion within 12 months. Using real time polymerase chain reaction and melting-curve analysis, we detected 13 single-nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
5
1
2
Order By: Relevance
“…In our study, the CC genotype of rs2228570 variation of VDR and the CA genotype of rs4588 variation of VDBP were found statistically high in patient group (p<0.05). Contrary to these findings, in a separate study no significant association was found between these polymorphisms with ISR (25,26).…”
Section: Discussioncontrasting
confidence: 80%
“…In our study, the CC genotype of rs2228570 variation of VDR and the CA genotype of rs4588 variation of VDBP were found statistically high in patient group (p<0.05). Contrary to these findings, in a separate study no significant association was found between these polymorphisms with ISR (25,26).…”
Section: Discussioncontrasting
confidence: 80%
“…To test this hypothesis and to limit confounding bias (latitude, etc), we focused on the countries whose DBP polymorphisms at rs7041 and rs4588 loci were defined and the allele frequencies reported in five cohort and two systematic review and meta‐analysis studies 8‐15 . We searched the literature for DBP gene polymorphism in each country.…”
Section: Methodsmentioning
confidence: 99%
“…To test this hypothesis and to limit confounding bias (latitude, etc), we focused on the countries whose DBP polymorphisms at rs7041 and rs4588 loci were defined and the allele frequencies reported in five cohort and two systematic review and meta-analysis studies. [8][9][10][11][12][13][14][15] We searched the literature for DBP gene polymorphism in each country. We recorded the total number of cases of COVID-19 and per million population in each of the countries to find the prevalence, and the mortality rates caused by the coronavirus infection recorded at 2nd July 2020 (Table 1) according to World Health Organization Coronavirus disease (COVID-19) Situation Report-164.…”
mentioning
confidence: 99%
“…Çalışmamızda risk faktörleri ile mutasyonlar arasındaki anlamlılık incelendiğinde diyabet hastalığı olan bireylerde rs1544410 mutasyonunun homozigot olarak bulunması durumunun istatistiksel olarak anlamlı olduğu belirlenmiştir. VDR gen varyantları ile aynı zamanda diyabet hastası olan KAH hastaları arasında olası bir ilişki olup olmadığını araştırmak için yapılan bir çalışmada ise Bsm1 polimorfizminin A alleli ile diyabetli KAH hastaları arasında istatistiksel açıdan anlamlı farklılık tespit edilmiştir (45).…”
Section: öZunclassified